2020
DOI: 10.1111/ajt.15816
|View full text |Cite
|
Sign up to set email alerts
|

New French heart allocation system: Comparison with Eurotransplant and US allocation systems

Abstract: | INTRODUC TI ONAlthough heart transplantation is the most effective treatment for selected patients with refractory heart failure, access to transplants remains limited by the shortage of heart donors. Currently, in France, the median posttransplant survival is 12 years, with two candidates for one graft and a 1-year waitlist mortality of 11%. 1 In this setting, the new French heart allocation system, implemented in 2018, was designed to minimize waitlist mortality and extend the donor pool while maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 10 publications
(10 reference statements)
0
52
0
1
Order By: Relevance
“…Our claim is that this flexible gravity model can be generalized to all organs and to different geographical context: indeed, it is used in France for heart 33,46‐48 and kidney 49,50 allocation schemes. Distance decays have also been calculated with a Poisson regression, based on observed data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our claim is that this flexible gravity model can be generalized to all organs and to different geographical context: indeed, it is used in France for heart 33,46‐48 and kidney 49,50 allocation schemes. Distance decays have also been calculated with a Poisson regression, based on observed data.…”
Section: Discussionmentioning
confidence: 99%
“…A major improvement added for heart transplants is calculation of the distance matrix 33 . Although distance between procurement centers and transplantation centers is still calculated in travel time by roads for the LAS, the heart allocation system is now calculated by travel time by roads if the distance is <200 km, otherwise by roads and private planes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that non‐compliance of immunosuppression use may lead to increased mortality in younger recipients which we could not assess 24 . Moreover, decisions to accept or reject a donor are highly selective as disease severity of recipient likely influences the quality of a donor deemed acceptable and this can potentially introduce some bias 25 . This study looks at a population who were offered transplant and cannot take into account those who were declined.…”
Section: Discussionmentioning
confidence: 99%
“…Some allocation schemes, such as the French Heart Allocation System, include an individual scoring system aimed at stratifying the risk of early posttransplant death. In the French system, transplant is contraindicated if the risk of death in the first year after HTx is greater than 50% 9‐11 . The development of a heart allocation score is a priority for the next revision to the Organ Procurement and Transplantation Network (OPTN) heart allocation system, and a score based on survival benefit is the most equitable.…”
Section: Introductionmentioning
confidence: 99%